Caracterização do período de instabilidade de órgãos vegetais submetidos à injúria mecânica - Albino, Ana Lúcia Seghessi (2011)
Mechanical injuries are a major cause of post-harvest losses, since they may cause metabolic and physiological changes in fruit and vegetables. However there are few studies that characterize the state of the tissue after injury and during the reaction of the tissue, which was called "Period of Instability (PI). In this work the objective was to characterize the "Period of Instability (PI) of tomatoes (Solanum lycopersicum L.) and kale leaves (Brassica oleracea v. acephala L.) after harvest, injured by puncture with different diameters. So, it was realized a tissues histological study of and plants water status analysis subjected to injury by puncture with diameters of 1.5 and 3.5 mm. Analysis of the structure of kale leaf and tomato injured tissues was performed using techniques of light microscopy during 9 and 24 days after harvest, respectively. The water status was evaluated by firmness of tomatoes, turgor pressure and firmness of the kale leaves. They were examined for 19 days in tomatoes and for seven days in kale leaves. Healthy tissues of tomatoes 'Carmen' showed uniform arrangement until the 16th day after harvest. In the tomato injured tissues PI there was adherence to the dead cell walls on the healthy cells. Puncture injuries with diameters of 1.5 and 3.5 mm did not change the firmness of tomatoes in 'Carmen' stored at 25°C, but the tomatoes firmness decreased after two days of post-harvest. The healthy leaves of kale showed degradation of cellular structures after nine days of harvest. The injured leaves by puncturing the 1.5 and 3.5 mm exhibited PI with physiological response, characterized by the accumulation of mucilage in the damaged region. Firmness and turgor pressure were not altered in the kale leaves injured stored at 5°C. However, healthy and injured leaves had a water recovery from the first to the second day after harvest, when stored in refrigerator at 5°C. After the water recovery, the treatments have a decreased of firmness and turgor pressure, and the injured groups showed variation in the values of firmness between the fourth and seventh day of post-harvest.